ChemInform Abstract: Iron(II)‐Catalyzed [2 + 2 + 2] Cycloaddition for Pyridine Ring Construction. Issue 19 (13th May 2014) - Richard, Vincent; Ipouck, Melinda; Merel, Delphine S.; Gaillard, Sylvain; Whitby, Richard J.; Witulski, Bernhard; Renaud, Jean‐Luc
Abstract The products are obtained in lower yields when aromatic nitriles are applied.